The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/ortho.ijortho_52_17
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of Internal Bone Transport Method for Reconstruction of Nonunion of Forearm

Abstract: Background: Defects of bone and soft tissue occur frequently after high-energy trauma, infections, and tumor resection. Treatment options are limited and outcomes are controversial in nonunion. Classical reconstruction methods are challenging. We describe a method of internal bone transport for treatment of complicated nonunion of the forearm. This method permits axial and internal bone transport without harming the distorted and complex neurovascular anatomy or soft-tissue envelope. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Bone transport techniques offer an effective solution to these problems. Demir et al 13 described an internal bone transport method for managing complex forearm bone discontinuities which allowed for axial and internal bone transport without damaging the intricate neurovascular anatomy or compromising the integrity of the soft tissue envelope. Their study encompassed five patients (mean age: 27 years) who presented with osseous nonunion of upper extremity bones (three ulna, two radius) and were successfully treated.…”
Section: Bone Transport Technique In Upper Extremity Bonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone transport techniques offer an effective solution to these problems. Demir et al 13 described an internal bone transport method for managing complex forearm bone discontinuities which allowed for axial and internal bone transport without damaging the intricate neurovascular anatomy or compromising the integrity of the soft tissue envelope. Their study encompassed five patients (mean age: 27 years) who presented with osseous nonunion of upper extremity bones (three ulna, two radius) and were successfully treated.…”
Section: Bone Transport Technique In Upper Extremity Bonesmentioning
confidence: 99%
“…Bone transport techniques offer an effective solution to these problems. Demir et al 13 . described an internal bone transport method for managing complex forearm bone discontinuities which allowed for axial and internal bone transport without damaging the intricate neurovascular anatomy or compromising the integrity of the soft tissue envelope.…”
Section: Bone Transport Technique In Upper Extremity Bonesmentioning
confidence: 99%
“…Eleven publications reported on the use of bone transport to reconstruct 82 forearm bone defects [33,34,35,36,37,38,39,40,41,42,43]. The majority of cases (n = 76, 91%) were performed for defects post-osteomyelitis debridement and all cases used external fixation for stabilization.…”
Section: Bone Transportmentioning
confidence: 99%
“…The majority of cases (n = 76, 91%) were performed for defects post-osteomyelitis debridement and all cases used external fixation for stabilization. One article by Demir et al reported their results of five patients who underwent forearm transport with an external fixator-based bone transport pulley system, similar to a cable transport apparatus [33,50]. Bone transport showed the highest complication rate of all reconstruction modalities although most of these (22/36, 61%) were superficial pin site infections.…”
Section: Bone Transportmentioning
confidence: 99%
See 1 more Smart Citation